SUPPLY CHAIN MANAGEMENT PRACTICES, AND INNOVATION ON MSME BUSINESS PERFORMANCE (Study on Craft MSMEs in the District Purworejo) - Annisa, Nenden Nur; Dwiantoro, Sigit; Wijayanti, Wijayanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Current era MSMEs are one of them business to be opportunity in increase rotation wheel economy in Indonesia. Various problem often influence performance MSME business among other advantages competitive, practical supply chain management and innovation. MSME actors not yet realize will importance superiority competitive For win the market. Things that haven't maximized that is practice supply chain management that has not applied in performance MSME business, apart from that's also a drawback do innovation that causes low performance MSME business. Objective from study This is For test influence superiority competitive to performance MSME business, test influence practice supply chain management towards performance MSME business, test influence innovation to performance MSME business. Population in study This is MSME owners in the Regency Purworejo . Taking sample use technique purposive sampling as many as 100 craft MSME owners in the Regency Purworejo. Instrument data collection uses questionnaire with use scale likert which was answered complet, appropriate criteria and meet condition validity and reliability . Analysis This use multiple linear regression with use SPSS 20.0 for Windows tools. Research result show that Superiority Competitive influential to Performance MSME Business, Practice Supply Chain Management has an influence To Performance MSME Business, and Innovation influential to Performance MSME Business.